Prevalence of suicide ideation among HIV/AIDS patients in China: A systematic review and meta-analysis - Li, Shiming; Yu, Shui; Yang, Queping; Yin, Jieyun; Zhu, Haohao; Jiang, Ying; Ji, Yingying (Frontiers in Public Health, 2023)
Objective A systematic review and meta-analysis was performed to evaluate the prevalence of suicide ideation among HIV/AIDS patients in China. Methods Systematic search of CNKI, Wanfang, China biology medicine database, Weipu, EMBASE, Web of science and PubMed for studies related to the suicide ideation of HIV/AIDS patients. The incidence of suicide ideation of HIV / AIDS patients in China was investigated by meta-analysis. Results A total of 16 studies were included (n = 6,174). The incidence of suicidal ideation in HIV/AIDS patients was 30.6% (95%CI: 21.4–39.9%). The results of subgroup analysis showed that the incidence of suicidal ideation in male was 36.1%, which was higher than that in female (32.8%), homosexual patients (39.7%) higher than heterosexual patients (27.1%), 2013–2021 survey (35.2%) higher than 2003–2012 survey (26.5%), the unmarried patients (39.6%) were higher than the married patients (34.5%), the patients diagnosed >1 year (28.4%) were higher than the patients diagnosed <1 year (27.6%), and the depression patients (34.3%) were higher than patients without depression (20.5%) and CD4 cell counts ≤200 cells/ul group (20.6%) were higher than those in >400 cells/ul group (19.8%). Conclusion The incidence of suicide ideation in HIV/AIDS patients in China is relatively high.